Characterisation of inhibitory activity of metabolites produced by six strains of Lactobacillus plantarum. - Foo, Hooi Ling; Karunakaramoorthy, Anuradha; Loh, Teck Chwen; Abdul Rahim, Raha; Nor Shamsudin, Mariana; Bejo, Mohd Hair
Antibiotics have been used as therapeutic agents and growth promoters in animal feeds since 1950, However, the excessive use of antibiotics has led to resistance in bacterial pathogens and re-occurrence of eradicated diseases, This situation has urged for the search of an alternative to antibiotics in livestock production, LAB as probiotic is known to produce a wide variety of antibacterial substances; as well as inhibitory metabolites, Therefore, the general objective of this study is to characterize metabolite produced by six strains of locally isolated Lactobacillus plantarum, The results of stability test showed that metabolites were able to tolerate a wide range of pH, stable at moderate temperature but able to retain activity at different storage temperatures. Inhibitory test was conducted by agar well diffusion assay on selected aquaculture pathogens for 63 combinations of metabolites subsequently (1; UL4, 2; TL1, 3; RI11,4; RG14, 5; RS5 and 6; RG11). Based on total scores, the best combinations were 12456, 123456, 12356 and 23456, The versatile characteristics of the studied metabolites reveal the potential of their application in livestock, aquaculture and food industries respectively.